ЕКСПРЕСІЯ ХЕМОКІНОВОГО (C-C МОТИВ) РЕЦЕПТОРА 7 (CCR7) В КЛІТИНАХ ЗЛОЯКІСНИХ ПУХЛИН ПЕРЕДМІХУРОВОЇ ЗАЛОЗИ ТА В МЕТАСТАЗАХ У ХВОРИХ МОЛОДОГО ВІКУ - Parra-Medina, R.; Payán-Gómez, C.; Acosta-Vega, N.L.; Ramírez-Clavijo, S. (PH Akademperiodyka, 2023)
Background: Chemokine (C-C motif) receptor 7 (CCR7) is a chemokine receptor involved in the carcinogenesis of several types of tumors due to its promoting action in epithelial-mesenchymal transition events, invasion, angiogenesis and metastasis. However, its role in prostate cancer (PCa) remains unclear. Aim: To evaluate CCR7 expression by immunohistochemistry in prostate tumors from young patients and to determine the possible relationship with the clinicopathological characteristics. Materials and Methods: We analyzed retrospectively paraffin-embedded tissue sections from 23 young PCa (≤ 55 years old) patients and evaluated the transcriptomic expression in the TCGA database. Results: Expression of CCR7 was observed in 15 cases (65%). The tissue samples from younger patients (≤ 50 years) were mostly positive in 72.7% (8/11) of cases. High grade GS (≥ 3) tumors were CCR7-positive in 71% cases. The malignant cells present in lymph nodes were CCR7 positive in 100% cases. The bioinformatic analysis showed a high CCR7 expression associated with the presence of metastasis (FC = 2.6, p = 0.03) in the Cancer Genome Atlas (TCGA) PCa cohort (PRAD). Conclusion: We showed that CCR7 expression in tumors from young patients is associated with the early onset of the disease and could also be related to lymph node metastasis.